Biotechnology Application of Individual and Multienzyme in Feed, and Its Effect on Broiler Growth Performance - Yanti, Amalia Firdaus; Mahfudhoh, Nimatul Laili Nur; Sajidan, S; Budiharjo, Agung (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2024)
Bromelain as a single enzyme is widely used as a meat tenderizer; however this can damage the meat cell’s. The effect of adding multienzyme Phyprozyme HP in feed is not yet known, so it needs to be investigated. This study aimed to evaluate the growth performance of broilers with the addition of single and multienzymes. This study used 42 Lohman MB 202 Grade Platinum broilers aged 21 to 35 days, using 6 treatments and 4 replications. P0 as the control feed. Bromelin was added in feed at the dose of P1: 600 GDU/kg, P2: 1200 GDU/kg, P3: 1800 GDU/kg, P4: 2400 GDU/kg, and P5: 3000 GDU/kg. Phyprozyme HP was added at P1: 0.19 g/kg, P2: 0.26 g/kg, P3: 0.33 g/kg, P4: 0.40 g/kg, and P5: 0.47 g/kg. Parameters measured included body weight, body weight gain, and carcass percentage. The results were analyzed using One-Way ANOVA. The addition of bromelain in feed decreased body weight, while the addition of multienzyme significantly improved broiler performance up to a dose of 0.33 g/kg feed. The addition of bromelain decreased carcass percentage to 11.07%, while the addition of multienzyme increased carcass percentage to 8.83%, but decreased it to 7.68% at the highest dose.